Ketidakpatuhan Tiongkok terhadap Sino-British Joint Declaration dalam Implementasi Kebijakan “One Country, Two Systems” Hong Kong - Putri, Cindy Claudia (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2023)
In general, this research discusses China's non-compliance with the Sino-British Joint Declaration agreement in implementing policies on the principle of "One Country, Two Systems" in Hong Kong. The interesting thing in this research is that the “One Country, Two Systems” system is a unique system of government because it has never been implemented in any country other than China. The Gap Research in this research is that China in the last ten years has shown an increasingly disobedient attitude towards the Sino-British Joint Declaration even though the agreement is a solution so that "One Country, Two Systems" can be carried out as it should. This non-compliance made China criticized by many countries but there was no intention of China to return to complying with the agreement. This research uses state security theory, state sovereignty theory, and compliance-based theory. With this theory, it can be seen what factors made China disobedient to the Sino-British Joint Declaration.Keywords: International Agreement, Democratization, One Country Two Systems, China, Hong Kong.